A Transformed Coordinate Model to Predict Tide and Surge Along the Head Bay of Bengal- Application to Cyclone of 1991 and 1970 - Hussain, Farzana (GANIT: Journal of Bangladesh Mathematical Society, 2016)
The head Bay of Bengal region is one of the most vulnerable regions for extreme water levels associated with severe tropical cyclones. The shallow nature of the head Bay, presence of a large number of deltas formed by major rivers and high tidal range are responsible for storm surge flooding in the region. Specifically, the rise and fall of tidal phases influence the height, duration, and arrival time of peak surge along the coast. The objective of the present study is to evaluate the tide-surge interaction during the super cyclone of 1991 and 1970. A transformed coordinate model is developed to estimate the possible water levels along the coast of Bangladesh. GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 7-25